Managerial Performance –Factors of Influence - Ion VERBONCU, Ph. D.; Ştefan-Florin CORCODEL (Revista de Management Comparat International)
In any social and economic system, performance is, in recent times, a term of reference for managers and workers, performance being a way of highlighting the objectives and the obtained results of the activity. An organization that is performancebased can take better advantage of the opportunities of the environment it is activating in, can easily overpass the difficulties that the environment puts forth, can quantitatively and qualitatively satisfy a segment of the social need in an superior way and can obtain the competitive advantage in the market in which it operates.